Mathematical Modeling of Thermal State Gas Samples in The Environmental Diagnosis Systems of Vehicle Engine - Поливянчук, А. П. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2017)
Purpose. Improving the accuracy of ecological diagnostic systems of transport engines – tunnels in the determination of one of the main indicators of toxicity engine exhaust gases - the mass emissions of particulate matter. Methods. Mathematical modeling, experimental studies, computational experiment, analysis and synthesis of information. Results. Analyzed: measuring technology for the mass emission of particulate matter, the tunnel classification, the effect of temperature of the sample gas before the filter for particulate sampling on the accuracy of the tunnels. Developed a mathematical model of the thermal state of the sample in the tunnel. Investigated the temperature sampling modes in the standard - full flow and alternative - mini- and micro-tunnels. Conclusions. Experiments confirmed the suitability of the developed mathematical model to determine the temperature of gas samples in different tunnels for different engine test modes. It is found that the temperature in the sampling mode minitunnel requires no correction, and it is necessary to adjust mikrotunnel and tunnel set corresponding to the reference.